Pulmonary and testicular tuberculosis in one patient caused by Mycobacterium tuberculosis with different genotypes - Yuanbo Lan; Ling Chen; Hong Zhang (Journal of Infection in Developing Countries)
Extrapulmonary tuberculosis (EPTB) accounted for 14% of 6.4 million cases of TB that were reported to WHO in 2017, and genitourinary TB (GUTB) is the second most common type of EPTB. The most common site of GUTB is the kidneys and testicular TB is relatively rare. The case of one patient with pulmonary and testicular TB caused separately by two different genotypes of Mycobacterium tuberculosis (Mtb) is further rare. Here, we present an unusual case of TB in which pulmonary TB (PTB) and testicular TB were caused by Mtb isolates with two different genotypes in a 91-year-old male patient from Zunyi, Guizhou Province of China. A better understanding of the mechanism by which a small number of tubercle bacilli are spread from the primary site of PTB to more distant parts/organs of the body, and what factors determine the potential EPTB site will provide us with new ways to prevent and control EPTB infections.